Analysis of the Mechanical Characteristics of Human Pancreas through Indentation: Preliminary In Vitro Results on Surgical Samples - Michele Pagnanelli; Francesco De Gaetano; Arianna Callera; Gennaro Nappo; Giovanni Capretti; Silvia Carrara; Alice Maria Renata Ferrari; Francesco Cellesi; Maria Laura Costantino; Alessandro Zerbi (Biomedicines, 2024)
Pancreatic surgery is extremely challenging and demands an extended learning curve to be executed with a low incidence of post-operative complications. The soft consistency of the human pancreas poses a primary challenge for pancreatic surgeons. This study aimed to analyze the preliminary mechanical characteristics of the human pancreas to develop a realistic synthetic phantom for surgical simulations in the near future. Pancreatic specimens, comprehensive of the pancreatic parenchyma and main pancreatic duct, were collected during pancreatic resections and analyzed through nano-bio-indentation (BioindenterTM UNHT3 Bio, Anton Paar GmbH, Graz, Austria) to measure the elastic modulus. Comparisons were made between slow and fast loading rates, immediate and post-freezing analyses, and multipoint indentations. The results demonstrated that a slow loading rate (30 μN/min), immediate analysis, and multipoint measurements are crucial for obtaining accurate values of the elastic modulus of the human pancreas (1.40 ± 0.47 kPa). In particular, the study revealed that analysis after freezing could impact the outcomes of the indentation. Moreover, the study suggested that both the pancreatic parenchyma and the main pancreatic duct should be analyzed to achieve a more precise and comprehensive definition of the. mechanical features of the pancreas. These preliminary findings represent the initial steps toward defining the consistency and mechanical characteristics of human pancreatic tissue with the goal of creating a realistic synthetic phantom.